Pneumococcal pulmonary valve endocarditis - Vrettos, Apostolos (Echo Res Pract, 2017)
Pulmonary valve endocarditis is a rare type of infective endocarditis (IE). Streptococcus pneumoniae is a pathogen that is uncommonly associated with IE. A 50 year-old male was referred to us after an incidental echocardiographic finding of a pulmonary valve vegetation. The patient had a recent admission for drainage of a scrotal abscess from which S. pneumoniae was isolated, complicated by hospital acquired pneumonia and pulmonary embolism. Analysis using polymerase chain reaction of the surgically resected mass revealed signs of 16S ribosomal DNA consistent with S. pneumoniae infection. This was an extremely rare case of pneumococcal pulmonary valve IE presenting entirely asymptomatically in the absence of any known risk factors. LEARNING POINTS: Streptococcus pneumoniae endocarditis can present with very few symptoms or even entirely asymptomatically, as in this case. Pulmonary valve endocarditis can affect healthy patients, even in the absence of any known predisposing risk factors or pre-existing heart conditions. An echocardiogram may be considered following severe infection with sepsis by pneumococci, to screen for vegetations that could evolve silently over the following weeks.